Social Media: Is it a Tool of Emancipation or a means for Harassment for Migrants? - Kumar, S Senthil (Journal of Advanced Research in Journalism & Mass Communication, 2018)
Recent incidents of lynching and killing ‘outsiders’ under various mysterious circumstances has one thing common for digital media and migrants: social media is the thread weaving toxic rumours which hurt migrants, who are labelled with the term ‘outsiders.’ Sometimes it is refugees. Sometimes it is internally displaced-within a city or across states. But all their fate is no different. The Pew Research Center calls global migration as one of the most “significant demographic trend” happening today. As per United Nation’s International Migration Report 2017, international migration is on the rise. From 173 million in 2000, 220 million in 2010, it has gone up to 258 million in 2017. War and internal strife in the Middle East is the single largest contributor for the global trend. But the same applies to Asian and South East Asian countries where the perennial issues of Bangladeshi migration, Rohingya migration from Myanmar, Afghan refugee issues, Sri Lankan Tamils migration in making Asia as no exception. But nation states aren’t the single most issue for the migrant issue. Because, people migrating within a country are also persecuted as ‘outsiders.’ Is the social media building bridges or destroying them? With 20 crore Indians using WhatsApp on a daily basis, it is becoming a parallel medium of spreading messages for the masses. But Mooer’s Law put forth by Calvin Mooer’s in 1959 is proving to be true in the digital era. He proposed that, “An information retrieval system will tend not to be used whenever it is more painful and troublesome for a customer to have information than for him not to have it.” Roger Summit, founder, Dialogue Information Services reinterprets for the era of social media: “information will be used in direct proportion to how easy it is to obtain”. This provides the answer to why people tend to believe in rumours spread by WhatsApp, without checking the veracity. Why two migrant labourers were thrashed as child kidnappers in Chennai? Why a migrant labourer from Uttar Pradesh was lynched in Tripura, suspecting her of child lifting? Since 10 May 2018 there have been 20 incidents of lynch killings, all motivated by rumours spread through social media. At the same time mobile devices act as a tool of communication and culture for migrants. Chandrahasan, Founder and Chairman of OfERR, an organisation working for rehabilitation of Sri Lankan refugees in their homeland says that social media plays a key role in uniting refugee children who were born and brought up in Tamil Nadu, without having a glimpse of their native land. “Their WhatsApp video calls showing lush greenery of the Sri Lanka is one of the key pushing points in re-integration with their home land” he says. The boom in mobile connectivity is bridging the gap between the migrants and their loved ones especially since 97% of migrants are men leaving behind their family in their homeland in search of better earning. The paper looks at how digital media and specifically social media could be a tool for emancipation at the same time a tool for harassment. How to cite this article: Kumar SS. Social Media: Is it a Tool of Emancipation or a means for Harassment for Migrants?. J Adv Res Jour Mass Comm 2018; 5(4): 143-147.